Mixed cation transport behaviours in electrodialysis during simultaneous ammonium enrichment and wastewater desalination - Yang, Dingchang (2022)
This study explored using electrodialysis (ED) to simultaneously enrich ammonium from wastewater for post nutrient recovery and desalt wastewater to enhance post-treatment for water recovery. It focused on the investigation of various factors affecting the efficiencies of ammonium concentration and cation removal and the elucidation of the mechanisms of mixed cation transport behaviours in ED. It was found that using an ED stack with the typical membrane arrangement (i.e., the cation exchange membranes (CEMs) are adjacent to electrode chambers), increasing applied current density and dilute solution/concentration solution volume ratio can generally increase the efficiency of ammonium concentration and the selectivity of NH4+ over other cations (i.e., Na+, K+, Ca2+ and Mg2+) by CEMs. However, the extent of such increases was constrained by severe ammonium leakage from the feedwater into the electrode solution. A total net transport number quantifying ion transport across ion exchange membranes was introduced to analyze ammonium leakage, which revealed that the less competitive migration of NH4+ than Na+ leads to the substantial accumulation of NH4+ in the electrode solution. To reduce ammonium leakage and increase the ammonium concentration efficiency, altering the membrane arrangement with the anion exchange membranes (AEMs) adjacent to the electrode chambers was demonstrated to be an effective strategy. This study provides important implications for developing ED-based technologies for nutrient enrichment and wastewater desalination.